Divergent effects of lure on multi-species camera-trap detections and quality of photos - Barcelos, DC; Costa Alvarenga, G; Gräbin, DM; Baccaro, F; Ramalho, EE (Elsevier, 2022)
The use of attractants to increase detection of target species, such as carnivores, in camera trap studies must be tested for its effectiveness and be carefully planned, as it can lead to misleading comparisons among species. We analyzed a five-year multi-species camera trap dataset of lured and control stations in a protected area in the Amazon rainforest. We aimed to identify the lure effect on a wider range of species and assess whether its use is an efficient strategy to increase the number and the quality of carnivore records. From the 14 vertebrate species analyzed, we found that the use of lures had a negligible effect on nine species, and did not improve the number of records or the detection probability of the carnivores. On the other hand, lured stations attracted omnivores and scavengers (common opossum, black-and-white tegu, and turkey vulture) while had the opposite effect on potential prey species (Black-capped capuchin and Northern Amazon squirrel). We detected a stronger effect of the lure when considering the number of records (relative abundance models) than the probability of detection (occupancy models). The lure increased the proportion of high-quality photos, suitable for individual recognition of jaguars, but only for the first weeks, when the lure was fresh. Therefore, we suggest that the sardine and egg-based lures should be refreshed every-two weeks to ensure greater effectiveness in the quality of photos for jaguar individualization. However, it is important to consider that lure renewing will imply a significant increase in field-related costs and it’s likely to bias other species studies. Thus, we advise that lures should only be used if researchers are certain that the focus is only to increase carnivore data at the expense of using non-target species. Camera traps survey design must be carefully planned a priori and the cost-benefit of lure use and refreshment should be weighed in the study context.